Development of Patient-Derived Preclinical Platform for Metastatic Pancreatic Cancer: PDOX and a Subsequent Organoid Model System Using Percutaneous Biopsy Samples - Choi, Sun Il; Jeon, A-Ra; Kim, Min Kyeong; Lee, Yu-Sun; Im, Ji Eun; Koh, Jung-Wook; Han, Sung-Sik; Kong, Sun-Young; Yoon, Kyong-Ah; Koh, Young-Hwan; Lee, Ju Hee; Lee, Woo Jin; et al. (Frontiers in Oncology, 2019)
Pancreatic ductal adenocarcinoma (PDAC) is the most lethal malignant tumor and more than 50% patients are diagnosed at metastatic stage. The preclinical model systems that reflect the genetic heterogeneity of metastatic tumors are urgently needed to guide optimal treatment. This study describes the development of patient-derived preclinical platform using very small sized-percutaneous liver gun biopsy (PLB) of metastatic pancreatic cancer, based on patient-derived xenograft (PDX)-mediated tissue amplification and subsequent organoid generation. To increase the success rate and shorten the tumor growth period, patient-derived orthotopic xenograft (PDOX) model was developed to directly implant threadlike PLB samples into the pancreas. The engraftment success rate of PDOX samples from 35 patients with metastatic PDAC was 47%, with these samples showing the potential to metastasize to distant organs, as in patients. The PDOX models retained the genetic alterations and histopathological features of the primary tumors. Tumor organoids were subsequently generated from first passage cancer cells isolated from F1 tumor tissue of PDOX that preserve the epithelial cancer characteristics and KRAS mutations of primary tumors. The response to gemcitabine of PDOX-derived organoids correlated with clinical outcomes in corresponding patients as well as PDOX models in vivo, suggesting that this PDOX-organoid system reflects clinical conditions. Collectively, these findings indicate that the proposed PDOX-organoid platform using PLB samples assessed both in vitro and in vivo could predict drug response under conditions closer to those found in actual patients, as well as enhancing understanding of the complexity of metastatic PDAC.